Strategi Kepolisian Resort Kota Bengkulu Dalam Mengurangi Kecelakaan Lalu Lintas Di Kota Bengkulu - Tri Purwanti (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
As population growth continues to increase, the transportation needs that support each person's journey will increase. The increasing number of motorized vehicles can pose a risk to traffic accidents. A strategy is needed to reduce traffic accidents in order to reduce the number of accidents in Bengkulu City. This strategy was carried out by the Bengkulu City Resort Police, especially Laka and Bengkulu City. This thesis aims to provide information and describe the strategy of the city of Bengkulu in reducing traffic accidents in the city of Bengkulu. This thesis reveals strategies in the form of counseling or socialization to the people of Bengkulu city. The research method used is a qualitative method with an inductive approach based on descriptive strategies that will clearly explain the strategy in reducing traffic accidents in the city of Bengkulu. Guided by Michael A Hitt's theory of Strategy Management Theory, namely human factors, vehicles, and the physical environment. The results of the study concluded that there were several strategies for the Bengkulu city police in reducing Bengkulu city accidents: 1) Conducting counseling to schools in the city of Bengkulu, 2) Notifying parents so that their children do not drive to school if they do not have a driver's license (SIM ), 3) Giving appeals on the road to the community, 4) Conducting counseling to motorcycle taxi drivers for orderly traffic, 5) Coordinating with relevant agencies such as Public Works and the Transportation Agency.